Maximizing Chlorobenzene Product Yield by Modifying The Benzene Chlorination Process - Syalom, Michael Natan; Danuwijaya, Fauzan Akmal; Rusully, Lalu Muhammad Imam; Aradhea, Muhammad Arif Tirtana (Journal of Chemical Engineering Research Progress, 2024)
Chlorobenzene is extensively used in the manufacture of phenol, aniline, and DDT; as a solvent for paints; and as a heat transfer medium. It is also occasionally used in the dry-cleaning industry. With the many uses of chlorobenzene, its production must have high efficiency both in terms of energy and mass in order to obtain maximum profits. In this paper, we will explain how to maximize chlorobenzene product yield by modifying the benzene chlorination process. The process modification was carried out by adding one distillation column unit and one mixer unit. Meanwhile, to carry out sensitivity analysis, case study tools on chemical engineering software were used. Based on process modifications, an increase in chlorobenzene yield was obtained from 83% to 98%. The results of the case study indicate that the higher the benzene pressure entering the reactor, the lower the yield of the liquid product exiting the reactor. Meanwhile, the higher the ratio of benzene mass flow to chlorine gas mass flow, the higher the yield of the liquid product exiting the reactor. Copyright © 2024 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).